The effects of dental status and chewing efficiency on the oral-health-related quality of life of nursing-home residents - Zenthöfer, Andreas; Ehret, Judith; Zajac, Melania; Kilian, Samuel; Rammelsberg, Peter; Klotz, Anna-Luisa (Clinical interventions in aging, 2020)
The Effects of Dental Status and Chewing Efficiency on the Oral-Health-Related Quality of Life of Nursing-Home Residents
Gesehen am 14.01.2021